Study on Evaluation Method of Water Injection Efficiency in Low-Permeability Reservoir - Qiang Yu; Xinjie Wang; Yifei Wang; Xingjiao Zhang (Geofluids)
Low-permeability reservoirs, especially ultralow-permeability reservoirs, usually show a problem of ineffective water injection which leads to low pressure with high injection-production ratio. It is urgent to determine the direction and proportion of ineffective water injection, so as to guide the adjustment of water injection development. Based on the theory of percolation mechanics and combined with the modern well test analysis method, the determination method of effective water injection ratio was established. This method can not only judge the direction of injected water but also determine the proportion of invalid injected water. This method was applied on typical oil reservoirs; the evaluation results showed that extremely low permeability and ultralow permeability usually exist the situation of water holding around the injected well which is almost 20% of the injected water. Some areas existed the water channeling; the evaluation results showed that the water channeling was closely related with sedimentary microfacies rather than microfractures, and the invalid injection accounts are about 45% of the injected water. The method is simple and feasible, which can provide technical reference for the development strategy adjustment of water drive development in low-permeability reservoir.